Description Of Community Knowledge Of Stunting In Galala Village, North Oba District, Tidore Islands City - Norma B. Toduho; Riskal Muslim; Andiani Andiani; Mayasari Soamole; Riska Alim; Rukmina Armain; Ayu Melisa Putri (UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
The cumulative impact of stunting is longterm malnutrition and recurrent infections in early childhood, especially occurring in the first 1000 days of life. This is defined as a child's height not appropriate for his actual age or a child who has of Z Score of the height body for the age >-2 standard deviations. This research uses descriptive analysis with a cross sectional study design. The total population is 1082 heads of families. The sample in this study was 292 heads of families obtained from sample calculations using the Slovin formula (alpha 0.05). Based on the results of descriptive analysis on the knowledge variable regarding stunting, it can be concluded that 147 people (50.3%) unknow about stunting, while 145 people (49.7%) know about stunting. Then in the overall stunting score column from the analysis results it was found that 182 people (62.3%) had good knowledge of stunting and 110 people (37.7%) were in the poor category. For the information source variable, it was found that 138 people (47.3%) received stunting information from health workers/cadres, 65 people from the mass media (22.3%), 64 people (21.9%) from other people. and family/parents as many as 25 people (8.6%). So it can be concluded that community knowledge and sources of information regarding stunting still need to be improved. It is hoped that there will be community involvement and collaboration with health workers, community leaders, religious leaders in efforts to increase knowledge about stunting in Galala Village.